The Contribution of The Strength of Leg Muscle and Eye-Hand Coordination Toward The Ability of Free Throws in Basketball - Novriansyah, Novriansyah; Nanda, Fitri Agung; Andrianto, Sigit Dwi; Rahmatullah, Muhammad Imam; Utama, Made Bang Redy (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
In playing basketball, a factor that has been ignored by the students is the effect of the strength of leg muscle and eye-hand coordination in shooting free throws. This research aims to know the contribution of the strength of leg muscle in the ability of free throws, the contribution of eye-hand coordination to the ability of free throws, as well as the contribution of leg muscle and eye-hand coordination in the ability of shooting free throws. This method used was the correlation method with product moment statistics and double correlation. The results of this research are: the contribution of the strength of leg muscle (X1) toward free throws (Y) gained 32,49%; the contribution of eye-hand coordination (X2) toward free throws (Y) was 40,96%; and the contribution of the strength of leg muscle (XI) and eye-hand coordination (X2) reached 51,84%. Based on the findings, it can be concluded that there are the contribution of the strength of leg muscle and eye-hand coordination toward free throws done by the students from 4th semester in Department of Physical Education Health and Recreation in Universitas Bengkulu when playing basketball.